Tautologies toponymiques : comment apprivoiser l’espace entre continuités et fractures - Fabio Armand; Jean-Pierre Gerfaud (EchoGéo)
Toponymic tautologies – denominations whose form condenses two expressions conveying one and the same concept – cannot be reduced to a simple etymological question. Beyond the need for an ever-renewed motivation for toponymic designations, they address the problem of contacts between populations and reflect the way these contacts have been established. From a shared geomorphological reality, i.e. the combination of geophysical and anthropized spaces, different languages and cultures can produce semantic partitions that aim to tame extra-linguistic space. The study of tautologies, which are part of a historical succession linked to the occupation of the places, represent a useful tool for identifying and formulating the issues of continuity and fracture that are at stake in our contemporary societies.